The Importance of a Conchal Bowl Element in the Fabrication of a Three-Dimensional Framework in Total Auricular Reconstruction - Young Soo Kim (Archives of Plastic Surgery, 2013)
Background To construct a sophisticated three-dimensional framework, numerous modifications have been reported in the literature. However, most surgeons have paid little attention to the anatomical configuration of the concha and more to its deepness and hollowness, leading to unsatisfactory outcomes. Methods For a configuration of the concha that is definitely anatomical, the author further developed and employed the conchal bowl element, which has been used by several surgeons although the results have not been published elsewhere. The author constructed the conchal bowl element in one of three patterns according to the amount of available cartilages: one block, two-pieces, or a cymba bowl element only. A total of 20 patients underwent auricular reconstruction using a costal cartilage framework between 2009 and 2012. The 8 earliest reconstructions were performed without a conchal bowl element and the latter 12 with a conchal bowl element. The patients were followed up for more than 1 year. The aesthetic results were scored by evaluating characteristics involving the stability of the crus helicis, the conchal definition, and the smoothness of the helical curve. Results The ears reconstructed early without a conchal bowl element showed a shallow and one or two incompletely separated concha with an obliterated cymba conchal space. They also did not have a realistic or smooth curve of the helix because of an unstable crus helicis. However, ears reconstructed later with the concha bowl element showed a definite crus helicis, deep cymba conchal space, and smooth helical curve. Conclusions The construction of the conchal bowl element is simple, not time-consuming procedure. It is suggested that the conchal bowl element must be constructed and attached to the main framework for natural configuration of the reconstructed ear.